1990
DOI: 10.1002/jcp.1041420228
|View full text |Cite
|
Sign up to set email alerts
|

Novel monoclonal antibodies identify antigenic determinants unique to cellular senescence

Abstract: Normal human diploid fibroblasts exhibit a limited lifespan in vitro and are used as a model to study in vivo aging. Monoclonal antibodies were generated against partially purified surface membranes from human diploid fibroblasts at the end of their lifespan (senescent). Three hybridomas were isolated that secreted antibodies reacting to cellular determinants expressed specifically on senescent human fibroblasts of different origin, including neonatal foreskin, embryonic lung, and adult skin punch biopsy, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Six normal human diploid ®broblast (NHDF) cell lines: HCA2 and Jas3, described in our previous studies (Noda et al, 1994;Porter et al, 1990), and WI26, TIG3, TIG7 and MRC5, provided by the Japanese Cancer Research Resources Bank (JCRB), were used for the p53-promoter analysis. T98G, a human glioblastoma cell line with homozygous mutant p53 gene status (at codon 237, Met to Ile, Ullrich et al, 1992), and HeLa S3, a human cervical carcinoma cell line, were also obtained from JCRB.…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
“…Six normal human diploid ®broblast (NHDF) cell lines: HCA2 and Jas3, described in our previous studies (Noda et al, 1994;Porter et al, 1990), and WI26, TIG3, TIG7 and MRC5, provided by the Japanese Cancer Research Resources Bank (JCRB), were used for the p53-promoter analysis. T98G, a human glioblastoma cell line with homozygous mutant p53 gene status (at codon 237, Met to Ile, Ullrich et al, 1992), and HeLa S3, a human cervical carcinoma cell line, were also obtained from JCRB.…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
“…Quantitative and qualitative changes in the synthesis of certain proteins [5][6][7][8] suggest that both efficiency and specificity of the biochemical machinery for protein synthesis may be different in senescent cells. These changes also affect the main components of extracellular matrix (ECM), such as fibronectin [9,10] and collagen [5,11]. We have found that the biosynthesis of proteoglycans (PG) is also modified with senescence [12], since late passage HFs incorporate greater amounts of radioactivity in the large PGs of the cell layer and show a lower ratio between PGs containing dermatan sulphate (DS) and those containing heparan sulphate (HS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the loss of proliferative capacity, senescent cells display a number of phenotypic changes, including an increase of cell size [5]and variations of extracellular matrix (ECM) components [6–9]. With reference to proteoglycans (PGs), senescent human skin fibroblasts (HFs) release into the growth medium an increased proportion of decorin and secrete PGs containing galactosaminoglycuronan (GalN‐GAG) moieties with a higher sulphation degree of galactosamine residues and a lower percentage content of totally unsulphated polysaccharide chains [10].…”
Section: Introductionmentioning
confidence: 99%